In vitro meningeal permeation of MnFe2O4 nanoparticles. (25th September 2018) - Mauro, Marcella; Crosera, Matteo; Bovenzi, Massimo; Adami, Gianpiero; Baracchini, Elena; Maina, Giovanni; Filon, Francesca Larese
Abstract: MnFe2 O4 nanoparticles (NPs) are commonly produced in some occupational settings and may reach high concentration in activities such as arc-welding or ferroalloy metallurgy. Manganese is an essential cofactor in enzyme activities but it has been demonstrated that long-term exposure to excessive levels can lead to "manganism", a neurodegenerative disease resembling Parkinson features. Inhaled NPs deposit partially in pharynx and nasopharynx and may reach the central nervous system through the olfactory nerve, which is completely enveloped by the meningeal membranes throughout its course from the nasal cavity to the olfactory bulb or through the trigeminal nerves. This study investigated in vitro the transmeningeal absorption of 50 nm MnFe2 O4 NPs, using excised porcine meninges mounted on Franz diffusion cells. We tested two donor solutions: the first containing MnFe2 O4 NPs (2.0 g/L) and the second obtained by the ultrafiltration of the first one, in order to test only the NPs water soluble fraction. Each experiment was carried separately for 4 h. Results showed that no Mn flux permeation through the meninges occurred, since only trace of the metal was found in receivers solutions of cells exposed to MnFeNPs (5.5 ± 2.2 ng/cm 2 ), ultrafiltered solution (3.5 ± 1.5 ng/cm 2 ) and blank cells. (2.1 ± 0.6 ng/cm 2) (mean and SE). Differences did not reach the statistical significance. Our study shows – for the first time - that MnFe2 O4 NPs penetrate the meningeal membrane in a negligible amount, thus making unlikely the hypothesis of a transcellular and paracellular absorption through the olfactory nerve but not excluding the hypothesis of an active intraneuronal absorption. Highlights: MnNPs are inhaled during arch welding processes, their potential intranasal absorption is poorly known. Mn in the basal ganglia of CNS could lead to neurological Parkinson-like syndrome. Our study investigated MnFe2O4NPs permeation through the meninges, which are involved in this absorption route. Results showed that a negligible amount of the metal pass through this membrane.